2021
DOI: 10.1037/hum0000156
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth as a process and an outcome: Vexing problems and paradoxes seen from the perspective of humanistic psychology.

Abstract: where he convenes the human flourishing research group. He is a registered psychologist specialising in psychotherapy. His areas of interest include personcentred psychology, positive psychology, and posttraumatic growth. He is the originator of the Organismic Valuing Theory of Growth following Adversity and author of What doesn't kill us: The new psychology of posttraumatic growth. The ideas in this article are all implicit in the Organismic Valuing Theory but are unpacked here in this article in greater dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…For example, a study that examined participants' coping with chronic illness reported that PTG has been related to positive health behaviors (such as healthier eating and exercise) and to increased adaption of positive coping strategies (Hamama‐Raz et al, 2019; Lim, 2019; Roepke et al, 2014). Another approach called for treating PTG not in relations to their outcomes, but focusing on the nature of growth process during crises and adversity (Joseph, 2019). In addition, a consideration of personality traits identified their relations to different PTG profiles (Taku & McLarnon, 2018).…”
Section: Posttraumatic Growthmentioning
confidence: 99%
“…For example, a study that examined participants' coping with chronic illness reported that PTG has been related to positive health behaviors (such as healthier eating and exercise) and to increased adaption of positive coping strategies (Hamama‐Raz et al, 2019; Lim, 2019; Roepke et al, 2014). Another approach called for treating PTG not in relations to their outcomes, but focusing on the nature of growth process during crises and adversity (Joseph, 2019). In addition, a consideration of personality traits identified their relations to different PTG profiles (Taku & McLarnon, 2018).…”
Section: Posttraumatic Growthmentioning
confidence: 99%
“…In order to experience post-traumatic growth, one must experience PTSD. This is highlighted in the work of Joseph et al [91,92] wherein they describe PTSD as the “engine” of post-traumatic growth. PTSD is the most studied psychosocial impact associated with disasters [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, and possibly due to the different discourses around posttraumatic growth mentioned above, many researchers seem to combine the outcomes of people experiencing different types of trauma into the one study: Some participants experiencing complex traumatic events are grouped with participants experiencing a singular traumatic event. Similarly, an illness ideology often clouds the overview of complex trauma and posttraumatic growth neglecting the biopsychosocial perspective that growth following adversity is a process of normal personality development that if nurtured, assists individuals build strength against future adversity and lead to more fulfilling functioning lives (Joseph, 2019). These studies offer consideration around study design providing insights for establishing both parameters and future research.…”
Section: Theoretical Backgroundmentioning
confidence: 99%